2020
DOI: 10.1136/jnnp-2019-322169
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to pallidal deep brain stimulation among monogenic dystonias: systematic review and meta-analysis

Abstract: ObjectiveGenetic subtypes of dystonia may respond differentially to deep brain stimulation of the globus pallidus pars interna (GPi DBS). We sought to compare GPi DBS outcomes among the most common monogenic dystonias.MethodsThis systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses and Meta-analysis of Observational Studies in Epidemiology guidelines. We searched PubMed for studies on genetically confirmed monogenic dystonia treated with GPi DBS do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 44 publications
3
75
1
Order By: Relevance
“…Despite early intervention with DBS, the multi-country cohort experienced suboptimal outcomes in the long-term. This result appears to be contradictory to the earlier dystonia studies reporting the association between better outcomes and shorter disease duration before DBS (Isaias et al, 2011;Lumsden et al, 2013;Artusi et al, 2020). In the suboptimal responders included in the historical cohort, only those with very long disease duration before DBS were reported to have fixed skeletal deformities, and age at onset was similar between these two groups.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Despite early intervention with DBS, the multi-country cohort experienced suboptimal outcomes in the long-term. This result appears to be contradictory to the earlier dystonia studies reporting the association between better outcomes and shorter disease duration before DBS (Isaias et al, 2011;Lumsden et al, 2013;Artusi et al, 2020). In the suboptimal responders included in the historical cohort, only those with very long disease duration before DBS were reported to have fixed skeletal deformities, and age at onset was similar between these two groups.…”
Section: Discussioncontrasting
confidence: 73%
“…In 2000, excellent DBS outcomes in patients with DYT1 were first reported by Coubes et al ( 2000 ). Subsequently, retrospective studies and a meta-analysis suggested that TOR1A mutation-positive status was a clinical predictive factor for a better DBS outcome (Vasques et al, 2009 ; Andrews et al, 2010 ; Borggraefe et al, 2010 ; FitzGerald et al, 2014 ; Moro et al, 2017 ; Artusi et al, 2020 ). Additionally, in the largest cohort to date of patients with DYT1 dystonia who underwent GPi DBS ( n = 47), improvement in dystonia severity by >80% was maintained up to 7 years after surgery (Panov et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical trials [49][50][51] have established the efficacy of GPi DBS in primary generalized dystonia, finding that those having the DYT1 gene mutation have a better response to DBS. 52 Anatomy. Relevant anatomy and imaging considerations of the sensorimotor portion of the GPi have been previously discussed (see PD section).…”
Section: Dystoniamentioning
confidence: 99%
“…6 DBS has recently been described as an effective therapy in ADCY5-related hyperkinesia, although clinical results seem to vary substantially. [7][8][9] Whether the heterogeneity of the benefit from DBS is attributed to additional genetic-related or operation-related factors (such as the exact electrode position) has to be explored in future clinical trials. Disclosures Ethical Compliance Statement: The authors confirm that the approval of an institutional review board was not required for this work.…”
Section: Discussionmentioning
confidence: 99%